Photobiomodulation therapy to treat neuropathic oral pain after contagion by COVID-19: Laser treatment of Neuropathic Pain after COVID-19 - Gomes, Fernanda Cruz; Naurath, Christian; Hiramatsu Azevedo, Luciane; Zezell, Denise Maria (Brazilian Dental Science, 2021)
Objective: The purpose of this short communication is to show that although photobiomodulation in thetreatment of neurophathic oral pain after COVID-19 contagion could be an option, photobiomodulation is nota new technique. PBMT was used with different protocols and pain was assessed using VAS (visual analoguescale - 0 until 10) before and after the consultation. Results: Evolution of VAS during the sessions showed adecrease in painful symptomatology as treatment was performed. Conclusion: Based on the results obtained inthe present case report, we concluded that PBMT with the parameters used in this clinical case was an effective,noninvasive and a new option of treatment for neuralgia resulting from COVID-19.KEYWORDSLaser; Photobiomodulation therapy; COVID-19; Oral neuralgia.